Risk of basal cell carcinoma in Swedish organ transplant recipients: a population‐based study. (21st December 2015) - Krynitz, B.; Olsson, H.; Lundh Rozell, B.; Lindelöf, B.; Edgren, G.; Smedby, K.E.
Summary: Background: Risk of basal cell carcinoma (BCC) has been reported to be several‐fold increased among organ transplant recipients (OTRs). However, due to lack of reliable BCC registration, population‐based risk estimates are scarce. Objectives: To characterize risk of BCC among OTRs compared with the general population, and contrast with risk of cutaneous squamous cell carcinoma (SCC). Subjects and methods: OTRs transplanted during 2004–2011 were identified through national healthcare registers and linked with the nationwide Swedish BCC Register initialized in 2004. Relative risk of BCC was expressed as standardized incidence ratios (SIR) with 95% confidence intervals (CI). Results: Altogether, 4023 transplanted patients developed 341 BCCs during follow‐up. Compared with the general population, the relative risk of BCC was increased sixfold (SIR 6·1, 95% CI 5·4–6·9). The risk was higher in kidney and heart/lung than in liver recipients (SIRkidney 7·2, 6·3–8·3; SIRheart/lung 5·8, 4·0–8·2; SIRliver 2·6, 1·7–4·0), and risk increased with time since transplantation ( P trend < 0·01). The SCC to BCC ratio was 1 : 1·7 and BCC developed earlier after transplantation than SCC. Distribution of anatomical sites and histological types did not differ substantially between OTR‐ and population‐BCCs. Conclusions: Risk of BCC was strikingly elevated in OTRs compared with the general population. Risk was higher in kidney recipients and increased with follow‐up time. These findings support a tumour‐promoting effect of immunosuppressive drugs in BCC development. The low SCC to BCC ratio was possibly attributed to short follow‐up time. Abstract : What's already known about this topic? Transplant recipients are at high risk of developing skin cancer, especially squamous cell carcinoma (SCC) but also basal cell carcinoma (BCC). Population‐based estimates of risk of BCC are scarce due to poor registration. What does this study add? The relative risk of post‐transplant BCC was increased sixfold compared with the background population, and most pronounced in kidney recipients. BCCs developed earlier after transplantation than SCCs. Linked Comment: Li, et al, Br J Dermatol 2016 ; 174: 16–17 .